2023
DOI: 10.3389/fpls.2023.1167238
|View full text |Cite
|
Sign up to set email alerts
|

Acetic acid positively modulates proline metabolism for mitigating PEG-mediated drought stress in Maize and Arabidopsis

Abstract: IntroductionOsmotic imbalance is one of the major consequences of drought stress, negatively affecting plant growth and productivity. Acetic acid has modulatory roles in osmotic balance in plants; however, the mechanistic insights into acetic acid-mediated osmotic adjustment under drought stress remains largely unknown.MethodsHere, we investigated how seed priming and seedling root treatment with acetic acid enabled maize plants overcoming polyethylene glycol (PEG)-induced drought effects.ResultsMaize seeds pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Another phenolic enzyme, PPO, plays a critical role in oxidizing phenols to quinones, contributing to plant stress tolerance [56,57]. Our results revealed heightened PPO expression levels in response to drought stress, consistent with research indicating the induction of PAL and PPO activities under stress conditions to bolster phenolics and flavonoids, thus reducing oxidative damage [19,37,50]. Furthermore, secondary metabolites, including phenols and flavonoids, were found to be substantially influenced by drought stress and genotype variations, with tolerant cultivars exhibiting higher concentrations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Another phenolic enzyme, PPO, plays a critical role in oxidizing phenols to quinones, contributing to plant stress tolerance [56,57]. Our results revealed heightened PPO expression levels in response to drought stress, consistent with research indicating the induction of PAL and PPO activities under stress conditions to bolster phenolics and flavonoids, thus reducing oxidative damage [19,37,50]. Furthermore, secondary metabolites, including phenols and flavonoids, were found to be substantially influenced by drought stress and genotype variations, with tolerant cultivars exhibiting higher concentrations.…”
Section: Discussionsupporting
confidence: 88%
“…•− and MDA concentrations by regulating osmotic solutes and enhancing antioxidant defenses, thereby preserving membrane permeability [49]. Compatible solutes like Pro play pivotal roles in maintaining osmotic potential and scavenging free radicals under drought conditions [37,41,50]. Our study indicated that the dramatic increases in soluble protein and Pro levels in PEG drought-stressed seedlings, with the susceptible genotype (QianKu-4) being more negatively impacted, highlighted its higher susceptibility to osmotic stress.…”
Section: Discussionmentioning
confidence: 71%
“…Hence, AFLP markers are exploited in characterizing genetic variability in olive cultivars and accessions (Ercisli et al 2009). Other studies manifested significant associations between DNA markers and morphoagronomic features in specific species (Kar et al 2008;Mesfer ALshamrani et al 2022;Safhi et al 2022;Mahmud et al 2023;Safhi et al 2023). To date, there is no report on the effect of high temperatures in Saudi Arabia on olive oil quality and purity criteria and the association of molecular markers with any of the studied characters.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural sectors, especially horticulture, are experiencing increased water demand (Selote and Khanna-Chopra, 2004). Under these conditions, the economic productivity of applied water in agricultural production should be increased (Mahmud et al 2023). Accordingly, olive production in Mediterranean regions that suffer from water scarcity is an ideal choice for cultivation in arid areas, especially newly reclaimed land, due to their high stress tolerance.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%